Acta Medica Philippina in Dr. Florentino B. Herrera, Jr. Medical Library College of Medicine University of the Philippines Manila, 1982-2012 a citation analysis - Vinzon, Minette R.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
The study analyzed the citations in the articles appended in Acta Medica Philippina, from 1982-2012. Specifically the study sought to: (a) determine the distribution of publication (type of document) such as journals, books, electronic sources, proceedings of conferences, seminars and meetings, reports and letters, theses/dissertations/unpublished materials used as reference in Acta Medica Philippina; (b) determine volume-wise distribution of citations; (c) study the authorship patterns in citations, and provide the most cited authors; (d) determine the age distribution of literature; (e) determine the obsolescence rate of periodical literature; (f) provide the most cited periodicals based on the frequency of use; (g) To determine the geographical (country-wise) distribution of literature, and; (h) determine the Journal Impact Factor of Acta Medica Philippina.
Results revealed that the most utilized type of publication was journals. More citations were from books and periodicals than the other types of materials. A total of 26 volumes (volume 18-46) with 8,454 citations were analyzed. The maximum citation per volume was 191, while the minimum was 1. Out of 526 citing articles, 72 have no citations. The maximum number of contributors/authors was 1,012 in 2010. the least number of contributors was 36 in 1999. The most popular contributing author is WHO. The top ten most popular foreign journal titles are: (1) Journal of Bone and Joint Surgery; (2) New England Journal of Medicine; (3) Lancet; (4) Cancer; (5) Journal of American and Medical Association; (6) Pediatrics; (7) British Medical Journal; (8) American Journal of Medicine; (9) Journal of Pediatrics, and; (10) The American Review of Respiratory Disease. For local Journals, the top ten most frequently cited are (1) Acta Medica Philippina; (2) Philippine Journal of Internal Medicine; (3) Philippine Journal of Science; (4) Journal of the Philippine Medical Association; (5) Philippine Journal of Surgical Specialties; (6) Philippine Journal of Microbiology and Infectious Diseases; (7) Philippine Journal of Pediatrics; (8) NRCP Research Bulletin; (9) Philippine Journal of Ophthalmology, and; (10) Philippine Journal of Obstetrics and Gynecology.
The most recent age of citation was -2 while the oldest age of citation is 98 years. At least fifty countries are actively contributing to the medical field. Journals published in the United States are most popular sources of citations with 62.2%.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Acta Medica Philippina; Dr. Florentino B. Herrera, Jr. Medical Library College of Medicine University of the Philippines Manila; Bibliographic citation; Biomedical materials